ANALYSIS OF STUDENTS’ MATHEMATICAL PROBLEM-SOLVING ABILITY IN SPLDV MATERIAL - Febriana, Rina; Delyana, hafizah (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2025)
This study aims to determine the mathematical problem-solving abilities of junior high school students on the topic of two-variable linear equation systems. The problem-solving ability indicators used in this study are in accordance with Polya's theory, namely understanding the problem, developing a solution plan, implementing the solution plan, and re-examining the procedure and results of the solution. The method used in this study is descriptive qualitative. The sampling technique in this study uses test and interview methods. Sampling is categorized into high, medium, and low groups and is taken based on teacher recommendations. The subjects of the study were grade VIII students of SMPN 03 VII KOTO Sungai Sariak, Padang Pariaman Regency. The instrument used in the study was a descriptive test of mathematical problem-solving abilities, totaling 5 questions. Data analysis used in this study was by grouping students based on high, medium, and low abilities. The results of this study indicate that students' mathematical problem-solving abilities are still in the low category because students are still unable to understand the problem first and are less able to re-examine the answers given by the teacher.